Investigation of a biosystem based on Arthrospira platensis for air revitalisation in spacecrafts: Performance evaluation through response surface methodology. (February 2021) - Soreanu, Gabriela; Cretescu, Igor; Diaconu, Mariana; Cojocaru, Corneliu; Ignat, Maria; Samoila, Petrisor; Harabagiu, Valeria
Abstract: Arthrospira platensis is featured as a promising microalgae candidate for the development of the biosystems for air revitalisation in spacecrafts and life support in space. An enhanced configuration of a sparged type photobioreactor (PBR), containing 5 L of A. platensis culture, which was equipped with an external LED lighting tube around the reactor, was used in this study. The PBR was operated under dynamic conditions (0.5 L/min) with synthetic air containing CO2 (400, 900, 1400 ppm) and other gas traces (NO2 1 ppm, SO2 2.5 ppm, acetic acid vapours 1 ppm), at various light intensities (1.5, 2.5, 3.5 klux), according to an experimental design. The removal of gas traces (NO2, SO2 and acetic acid vapours) was below the detection limit (e.g. above 90% removal efficiency), while the removal of CO2 ranged between 69% and 85%, depending on the initial CO2 concentration and the light intensity. Thus, the system is able to roughly decrease the contaminant concentration from 1 ppm to below 0.1 ppm for NO2, 2.5 ppm to below 0.1 ppm for SO2, 1 ppm to below 1 ppb for acetic acid vapours and from 1400 ppm to 370 or from 400 ppm to 60 ppm for CO2 . The system performance was thus subject to mathematical modelling and optimization in terms of CO2 removal efficiency and CO2 elimination capacity, which were also corroborated with the power consumption for illumination. Highlights: A. platensis is screened as a microalgae candidate for environment control in space. Air contaminated with multiple trace gaseous contaminants is addressed. Next-generation lighting technology is involved as illumination alternative. Biosystem diagnosis is efficiently performed via mathematical tools. More than 80% contaminants removal can be achieved.